Precarization of Labor in Capitalist Society: A Historical and Conceptual Rescue (Interdisciplinary Studies Journal, 2021)
This article aims to reflect on the category of labor in capitalist society, seeking to clarify its contradictory dimensions. The text was developed based on the final thesis of the undergraduate Social Work course at the Federal University of Pampa, in 2017. It starts with the following question: How is the process of labor precarization configured in contemporary society? To meet the proposed objective, the study was based on critical social theory from a Marxist perspective, through bibliographical research. In this perspective, it intends to contribute with subsidies to strengthen the debates on this topic and with the resistance processes of the working class. It is understood that from the development of the capitalist mode of production, processes are established that seek to regularize the productive dynamics of capital, which involve increasing material production through labor management models that meet the expansion of capital. Thus, to deepen such themes, the study will address: a) labor and its historical-ontological meaning; b) the historical context involving slave labor to free wage labor; c) the transition from Fordism/Taylorism to Flexible Accumulation/Toyotism and the processes of labor precarization. At the end of the study, the multiple contradictions that erupted under the logic of the market were evidenced, causing serious repercussions in the labor world. As a result, labor precarization materializes in the exploitation of labor power, expropriation of surplus value, reproducing the social relations of the capitalist mode of production in order to serve the logic of the market.
Keywords: Work; Precarization of Work; Capitalism